Pengaruh Budaya Kerja, Beban Kerja, dan Disiplin Kerja terhadap Kinerja Karyawan Pada Kantor Pusat PT Jaya Konstruksi Manggala Pratama Tbk - Ariyanto, Bintoro; Sari, Atika (Management Research and Business Journal, 2025)
This research aims to examine and analyze the influence of work culture, workload and workdiscipline on employee performance at the Head Office of PT Jaya Construction Manggala PrtamaTbk. Data collection was carried out through distributing questionnaires given to 101 employeesat PT Jaya Construction Manggala Pratama Tbk. The data analysis used in this research is aquantitative method using multiple regression analysis. The research results show that workculture and work discipline variables have a significant effect on employee performance, whileworkload does not have a partial significant effect on employee performance. The threeindependent variables have a significant effect on employee performance together.